Mathematics performance of students with mild mental retardation and medium of instruction - Chuabio, Katherine A. (2005)
This experimental research determined the effects of medium instruction on the math performance of thirty-six grade 3 students with mild mental retardation from a public school. The sample was divided into English and Filipino groups. Findings showed that students from both groups significantly improved after the experiment, and that the mathematics performance of the students was not significantly different when the test was written in either English or Filipino. However, in the aspect of solving word problems, the English group did significantly better when questions were expressed in Filipino. The study also showed that there was no significant difference between the Filipino group and the English group in all aspects of mathematics performance.
"March 2005."
Thesis (M.A. Special Education)--University of the Philippines Diliman.
Keywords: Children with mental disabilities -- Education -- Philippines -- Tondo (Manila); Mathematical ability in children -- Philippines -- Tondo (Manila); Mathematical ability -- Testing